2016
DOI: 10.1109/tasc.2016.2517628
|View full text |Cite
|
Sign up to set email alerts
|

Magnetization and Demagnetization Studies of an HTS Bulk in an Iron Core

Abstract: High Temperature Superconductors (HTS) are promising materials in variety of practical applications due to their ability to act as powerful permanent magnets. Thus, in this paper, we have studied the influence of some pulsed and pulsating magnetic fields applied to a magnetized HTS bulk sample. The bulk sample, the iron core, the two inductors and the current sources used to magnetize and demagnetize the superconducting bulk in the iron core are presented. Then, we detail various magnetizing and demagnetizing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…For practical applications, the demagnetization rates of trapped field magnets need to be estimated to determine whether or not re-magnetization is required. The demagnetization of 2G HS bulks and stack of YBCO tapes have been studied extensively, with both perpendicular and parallel magnetic fields [39,40,41,42]. Strategies to suppress the demagnetization have been proposed using shielding rings [43,44].…”
Section: . Demagnetizationmentioning
confidence: 99%
“…For practical applications, the demagnetization rates of trapped field magnets need to be estimated to determine whether or not re-magnetization is required. The demagnetization of 2G HS bulks and stack of YBCO tapes have been studied extensively, with both perpendicular and parallel magnetic fields [39,40,41,42]. Strategies to suppress the demagnetization have been proposed using shielding rings [43,44].…”
Section: . Demagnetizationmentioning
confidence: 99%
“…GREEN lab studied the magnetization of HTS bulk in an iron core (Figure 7), and they concluded that the trapped magnetic field in the HTS bulk increased and the current of the optimal pulse decreased. Therefore, iron around the HTS bulk improved the magnetization process [29,30] One of the issues with this kind of HTS motor is the choice of whether to magnetize the HTS bulks inside the machine (in situ) or outside of the machine (ex situ). The prototypes already made used ex situ magnetization because it is the simplest option in terms of magnetization.…”
Section: Hts Permanent Magnet Machinementioning
confidence: 99%
“…A suitable magnetization method exists called pulse field magnetization (PFM). In this method, the HTS YBaCuO bulk is cooled down and then submitted to magnetic field pulses [ 28 , 29 , 30 ]. It traps less of the magnetic field than the ZFC method but it requires only a small copper magnetization coil.…”
Section: Hts Bulk Application In Electrical Machinesmentioning
confidence: 99%
See 1 more Smart Citation
“…Conventional PM blocks with unity recoil permeability were used. Only the 'equivalent' remanent flux density of the blocks was varied to represent the high fields produced by the superconducting bulks [10], [18] or stacks of superconducting tapes [19].…”
Section: Superconducting Machine Designmentioning
confidence: 99%